Effect of pH and Temperature on Copper ions Adsorption from Aqueous solutions into Iron Slag (Sebha University Conference Proceedings, 2024)
Heavy metal pollution has become one of the most important environmental problems. Heavy metal pollution has properties that accumulate in nature and cannot be degraded. The aim of this work is to study the effect of pH and temperature on the effectiveness of iron slag in removing copper ions from aqueous solutions. The results indicated that the best removal of copper ions was at temperature (25 °C), weight of the adsorbent (3.5 g), and pH (5). The best removal percentage was (99.55 %) at the initial concentration of the solution. From these results iron slage can be used as reliable remover of copper ions from wastewater and industrial wastewater